A clinical case of autosomal recessive agammaglobulinemia with B-cell deficiency - E. V. Negodnova; M. S. Iskandyarova; E. N. Tyagusheva; O. A. Radaeva; G. V. Fominova (Association of Paediatric Allergists and Immunologists of Russia (APAIR), 2024)
Background. Primary agammaglobulinemia is the result of specific changes in B-cells that lead to low antibody production. A preliminary diagnosis is established if there is a history of frequent bacterial infections (otitis media, sinusitis, skin abscesses), including severe course, in some cases caused by opportunistic flora and atypical mycobacteria; low levels of immunoglobulins. The main symptoms of primary immunodeficiency in a child from this clinical example were frequent recidivating bronchial obstruction with the development of pneumonia.Presentation of the clinical case.The publication presents a clinical case of autosomal recessive agammaglobulinemia with B-cell deficiency in a child of 2 years, 7 months. During the follow-up period from 4 months to 2 months, 7 months, the child had 3 episodes of pneumonia, 3 episodes of purulent otitis media. The child repeatedly underwent inpatient treatment, where he received broad-spectrum antibiotics as treatment. Based on the examination (IgA (0.02 g/l), IgG (0.3 g/l), IgM (0.07 g/l) and the absence of CD19+ cells), the diagnosis of "Primary immunodeficiency, agammaglobulinemia" was made, which was subsequently confirmed by the RDC of Moscow. From the moment of diagnosis, the child receives intravenous immunoglobulins at a dose of 7.5 g. and antibacterial therapy.Conclusion. Early recognition and diagnosis of these conditions is crucial to improve outcomes and prevent complications.